Can the judo training improve the muscle-skeletal acting in older women with low bone mineral density? - Borba-Pinheiro, Cláudio Joaquim; De Figueiredo, Nébia Maria Almeida; De Alencar Carvalho, Mauro César Gurgel; Drigo, Alexandre Janotta [UNESP]; Dantas, Estélio Henrique Martin (Asociacion Espanola de Analisis del Rendimiento Deportivo, 2013)
Osteoporosis is a bone disease that causes bone fragility with increased risks of fractures and negative consequences on human mobility. The planned and monitored physical activity by professionals have shown good results on bone density, body balance and quality of life, factors that are determinants to the functional autonomy and independence of older women. The exercises and techniques realization of adapted judo are of low difficulty, emphasizing the development of motor coordination, muscle strength, body balance and consequently the bone density. Thus, the objective of this work is to present the adapted judo training as a physical activity alternative for older women with low bone density, demonstrating that the adaptation of judo training with professional supervision can help maintain bone density and other related-variables listed in this population. © Faculty of Education. University of Alicante. © 2013 University of Alicante.
Keywords: Adapted physical activity; Bone health; Health care